The Effects of the KCNQ Openers Retigabine and Flupirtine on Myotonia in Mammalian Skeletal Muscle Induced by a Chloride Channel Blocker. (25th March 2012) - Su, Tzu-Rong; Zei, Wen-Shan; Su, Ching-Chyuan; Hsiao, George; Lin, Min-Jon
Abstract : The purpose of this study was to investigate the effect of KCNQ (potassium channel, voltage-gated, KQT-like subfamily) openers in preventing myotonia caused by anthracene-9-carboxylic acid (9-AC, a chloride channel blocker). An animal model of myotonia can be elicited in murine skeletal muscle by 9-AC treatment. KCNQ openers, such as retigabine and flupirtine, can inhibit the increased twitch amplitude (0.1 Hz stimulation) and reduce the tetanic fade (20 Hz stimulations) observed in the presence of 9-AC. Furthermore, the prolonged twitch duration of skeletal muscle was also inhibited by retigabine or flupirtine. Lamotrigine (an anticonvulsant drug) has a lesser effect on the muscle twitch amplitude, tetanic fade, and prolonged twitch duration as compared with KCNQ openers. In experiments using intracellular recordings, retigabine and flupirtine clearly reduced the firing frequencies of repetitive action potentials induced by 9-AC. These data suggested that KCNQ openers prevent the myotonia induced by 9-AC, at least partly through enhancing potassium conductance in skeletal muscle. Taken together, these results indicate that KCNQ openers are potential alternative therapeutic agents for the treatment of myotonia.